Mothers, teachers, peers, and the gender gap in early math achievement - Pedro Carneiro; Yyannú Cruz Aguayo; Norbert Rüdiger Schady (Inter-American Development Bank (IDB), 2018)
We study the determinants of math achievement among children in early elementary school using data from a unique experiment in which children were randomly assigned to classrooms within schools for four consecutive grades. As a result, each child in our sample was exposed to four separate, orthogonal shocks to the quality of teachers and peers. We first show that there are steep socioeconomic gradients and a substantial boy-girl gap in math test scores. However, among children of mothers with university education, there is no difference in the math achievement of girls and boys. We use the experimental design to test for differences in how boys and girls respond to different measures of the quality of their classrooms, teachers, and peers. We find no evidence of differential responses by gender.
Keywords: I21; 330; test scores; teachers; gender